2004
DOI: 10.1063/1.1655685
|View full text |Cite
|
Sign up to set email alerts
|

Field emission and photofluorescent characteristics of zinc oxide nanowires synthesized by a metal catalyzed vapor-liquid-solid process

Abstract: Articles you may be interested inOn the origin of enhanced photoconduction and photoluminescence from Au and Ti nanoparticles decorated aligned ZnO nanowire heterostructures The ZnO nanowires synthesized by vapor-liquid-solid growth mechanism with Cu and Au as the catalyst were investigated. The principal differences in morphology between Cu and Au catalyzed ZnO nanowires are observed and lead to significant differences in their field emission and photofluorescent characteristics. The Cu catalyzed ZnO nanowire… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
83
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 181 publications
(88 citation statements)
references
References 24 publications
4
83
0
Order By: Relevance
“…Several scientific works have reported the use of catalysts, such as nanoparticles of Au or other metals, deposited directly onto substrates to selectively grow nanorods and nanowires [20,[58][59][60][61][62][63]. In fact, on an amorphous surface or under lattice mismatching conditions, ZnO nanowires tend to grow in random directions.…”
Section: Thermally Activated Chemical Vapor Depositionmentioning
confidence: 99%
“…Several scientific works have reported the use of catalysts, such as nanoparticles of Au or other metals, deposited directly onto substrates to selectively grow nanorods and nanowires [20,[58][59][60][61][62][63]. In fact, on an amorphous surface or under lattice mismatching conditions, ZnO nanowires tend to grow in random directions.…”
Section: Thermally Activated Chemical Vapor Depositionmentioning
confidence: 99%
“…7 In fact, there are some reports on FE from nanostructural ZnO. [8][9][10][11] Some researchers even coated ZnO nanoparticles on the CNT surface to improve the FE performance. 12,13 Although many valuable results have been reported, the general methodologies of realizing an effective ZnO field emitter have not been revealed.…”
Section: Introductionmentioning
confidence: 98%
“…It is a versatile smart material that has unique applications in catalysts, sensors, piezoelectric transducers and actuators, photovoltaic, and surface acoustic wave devices [3]. ZnObased one-dimensional nanostructures in various forms including nanowires [4][5][6][7][8], nanoneedles [9][10][11], nanopins [12], nanorods [13], nanopencil [14], and tetrapod-like nanostructures [15,16] have attracted considerable attention for application as room temperature UV lasing emission source, as electron emitting sources, gas sensors, as field effect transistors, and so on. The field emission test results of these ZnO nanostructures showed that electrons are more easily emitted from nanostructures with sharp tips [9-16] than nanostructures with a uniform diameter [5][6][7].…”
Section: Introductionmentioning
confidence: 99%